Funcionarios Mario Alfaro, Kenneth Robles, Javier Arguedas, Gerardo Campos, Pablo Navarro, Luis Marín, Carlos Agüero, Edgar Castro, Marlen Musio, Juan Arturo Picado, Omar Arroyo. - Universidad Estatal a Distancia (San José, Costa Rica : UNED, 2025)
Grupo grande de personas
Colección Fototeca UNED
Keywords: Alfaro, Mario; Robles, Kenneth; Arguedas, Javier; Campos, Gerardo; Navarro, Pablo; Marín, Luis; Agüero, Carlos; Castro, Edgar; Musio, Marlen; Picado, Jorge Arturo; Arroyo, Omar; FOTOGRAFÍAS; UNIVERSIDAD ESTATAL A DISTANCIA -- COSTA RICA; FOTOTECA